The Research and Development of iFTEM Fixed-wing Airborne Time-domain Electromagnetic System - Lu, Ning; Zheng, Hongshan; Li, Junfeng; Huang, Wei; Liu, Yu; Li, Fei; Meng, Qingmin; Zhi, Qingquan; Wang, Xingchun (Research Advances in Environment, Geography and Earth Science Vol. 10, 2024)
In this article, the iFTEM-I system was introduced and its effectiveness was verified by comparing airborne and ground TEM surveys. Fixed-wing time-domain electromagnetic (FTEM) surveying has been widely applied globally in metal ore exploration and groundwater mapping. In recent years, its application in China has also gradually become popular. The fixed-wing time-domain electromagnetic system (iFTEM) developed by the Institute of Geological and Geochemical Exploration (IGGE) has been developed into a second-generation product (iFTEM-II) and has completed field verification. This paper introduces the working principle and system parameters of iFTEM. The comparison results between iFTEM-I and the ground TEM system (TEM-30B) present that the effective prospecting depth of iFTEM-I is about 350 m. The iFTEM-II utilized a new aircraft with an 8-ton load and a larger current supply. Therefore, its transmitter moment exceeds twice that of the iFTEM-I. After verification of the results of a hydrogeological survey, the detection depth of iFTEM-II has reached 600m.